PERNIKAHAN DINI DAN PENGARUHNYA TERHADAP KETAHANAN KELUARGA DI KECAMATAN AIR HANGAT TIMUR KABUPATEN KERINCI - Ali Hamzah; Y Sonafist; Ahmad Yani (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2020)
Marriage creates a balance of one's life biologically, psychologically and socially. Biologically, sexual needs are met. Psychologically, mental maturity and emotional stability, determine the diversity of married life. Marriages that are too young will result in a rise in divorce cases due to a lack of awareness to be responsible in married life. Sociologically, marriage makes a man and a woman legally considered legal. A lasting marriage is characterized by the husband and wife's readiness to assume responsibilities. According to the Marriage Law No. 16 of 2019 paragraph (7) states that marriage is performed if the male party has reached the age of 19 years and the woman is 19 years old provided that there must be permission from the parents. However, if there is something that deviates from the Law for example because of the free association of a pregnant woman outside of marriage and the woman has not reached the age of 19 years and the man has not reached the age of 19 years then Law No. 16 of 2019 can still provide the possibility of the age limit that has been set by the dispensation of marriage to the Court or other officials appointed by both parents of the women and the male side , this is based on article 7 paragraph 1 of the Marriage Law No. 16 of 2019.